Effect of abrasive pre‐treatment on drying rate of grape berries and raisin quality. Issue 9 (28th July 2021) - Pawar, Dilip Ananda; Giri, Saroj Kumar; Sharma, Ajay Kumar; Kotwaliwale, Nachiket
Abstract: Drying of grapes for the production of raisins is a slow and complex process. The prevalent chemical pre‐drying treatment involves the use of chemicals which trigger food safety issues and such a method also takes a longer drying time for grapes. A novel industrial‐scale abrasive pre‐treatment system was developed and its operating parameters were optimized. The physical pre‐treatment system consists of the rotating drum with its inner surface of specific abrasive protrusions. Optimized parameters using Box–Behnken design of response surface methodology as operating speed (15.13 rpm), treatment time (3.27 min), and sample size (8.45 kg), resulted in maximum treatment efficiency (97.76%), and minimum drying time (65.5 hr) for grape. The waxy cuticle layer was removed physically from the surface of grapes and hence the drying rate was found enhanced compared to chemical pre‐treatment. Abrasive pre‐treatment produced better quality raisins except slightly higher browning index (29.64 ± 1.53) compared to chemical pre‐treatment (26.19 ± 0.93). Novelty impact statement: The study is about a chemical chemical‐free process and equipment for the production of grape raisins with abrasive pre‐treatment. Enhanced drying of grapes by abrasive pre‐treatment (27.77% less drying time) compared to chemical pre‐treatment. Developed industrial scale raisin making process has the potential to produce good quality, safe raisins without the use of chemicals and the process is environmental friendly.